The ecological footprint of outdoor activities Factors affecting human-vectored seed dispersal on clothing - Lukács Katalin; Tóth Ágnes; Kiss Réka; Deák Balázs; Rádai Zoltán; Tóth Katalin; Kelemen András; Bátori Zoltán; Hábenczyus Alida Anna; Tölgyesi Csaba; Miglécz Tamás; Godó Laura; et al. (2024)
In the Anthropocene, humans are among the most abundant long-distance seed dispersal vectors globally, due to our increasing mobility and the growing global population. However, there are several knowledge gaps related to the process of human-vectored dispersal (HVD) on clothing. In a multi-site field experiment covering various habitat types in three countries of Central-Europe, we involved 88 volunteer participants and collected 251 HVD samples and 2008 subsamples from their socks and shoes. We analysed the number of diaspores and species in the samples. Specifically, we studied the effects of site characteristics (variables related to habitat types and season), vector characteristics (activity type, gender, clothing type, shoe type) and plant characteristics (species pool of the visited habitats and plant traits) on the number of diaspores and array of species dispersed. We assessed the habits of people that could be relevant for HVD with a questionnaire survey. A total of 35,935 diaspores of 229 plant taxa were identified from the samples, which indicates a huge potential of HVD in dispersing diaspores across habitats and regions. Most diaspores were recorded in grassland habitats, and more diaspores were dispersed during fieldwork than excursions. Clothing type also played a decisive role: there were more diaspores and species when wearing short-top shoes and short trousers than long ones. Even though our study was carried out mainly in natural or semi-natural habitats, a large number of dispersed species were disturbance-tolerants and weeds and only a few were specialists, suggesting the controversial role of HVD in conservation. At the individual level, people can reduce the number of diaspores through their clothing choices and diaspore removal habits, while providing adequate equipment for staff, operating cleaning stations, and increasing awareness of employees are main ways in which unintended diaspore dispersal can be tackled at the institutional level.
Keywords: Biológiai tudományok